Design of Ground Distributed Core Network Architecture for Large Low Earth Orbit Communication Constellation - YIN Shuming; HAO Liyun; GUO Haoran; XUE Chengcheng (天地一体化信息网络)
Currently, satellite communication systems mainly deploy core networks in a centralized manner, which poses risks of single point failure and limits system reliability, scalability, and overall performance. The large-scale low-orbit constellation communication system has seen a significant increase in the number of users and business volume, which puts higher demands on system reliability and overall performance. In response, a multi-node distributed ground core network architecture based on the typical layout of low-orbit constellation "space-based base station + ground core network" was proposed. The solutions to the problems of landing selection and user management in multi-node core networks for low-orbit constellations were proposed, and basic processes for user roaming and active/standby switching were designed. The distributed core network had the ability to share services and backup, which alleviated the load pressure of single-node core networks and improved system reliability and overall performance.